Informatyzacja urzędów gmin w świetle wyników badań ankietowych - Goleń, Marek J. (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
The development of the information society forces local governments to improve their activities by informatization in order to provide administrative services electronically round the clock and 7 days a week. The paper presents the general model of the completely informatized self-government office and describes the results of the poll research on the informatization of the communes' offices.The research has revealed very low standard of the informatization of the communes' offices in Poland. The author of the paper has made an attempt to identify reasons of that condition and he has pointed at proposals of the manners to improve the situation. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1083, s. 734-741